Musemes in affect. Philip Tagg’s model of music analysis - Zielonka, Stefania (Interdisciplinary Studies in Musicology, 2020)
The paper is an attempt to synthesize the most important aspects of a model of popular and film music analysis proposed by British musicologist Philip Tagg. Tagg, using the category of musemes – universal meaning units, isolated from the musical structure of the composition on the basis of criteria established for every given case – examines selected pieces using multi-level semiotic analysis. In his model Tagg takes into account both the importance of the broadly understood cultural context and the intertextuality of the piece. He also emphasizes the role of affect in musical communication, which is necessary to fully understand the meaning of a musical work.